2015
DOI: 10.1177/1526602815580308
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Ultrasound Measurements After Drug-Eluting Stent Placement in Femoropopliteal Lesions

Abstract: IVUS guidance of DES placement in femoropopliteal lesions can offer useful predictors of restenosis at 1 year. The utility of distal lumen CSA and the axial symmetry index in the prediction of restenosis after femoropopliteal DES placement should be confirmed in a larger cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…Several studies revealed that the distal reference lumen/EEM CSA was useful to predict TLR after stent implantation for FP lesions 16, 18, 19) , which is consistent with our results. The results of the present study suggest that restenosis risk after EVT for long occlusive lesions with small vessel is high.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies revealed that the distal reference lumen/EEM CSA was useful to predict TLR after stent implantation for FP lesions 16, 18, 19) , which is consistent with our results. The results of the present study suggest that restenosis risk after EVT for long occlusive lesions with small vessel is high.…”
Section: Discussionsupporting
confidence: 92%
“…The definition of stent thrombosis was the same as described elsewhere 18) . The definitions of IVUS parameters followed those of a previous report 19) . Wire passage in occlusive lesions was classified according to IVUS findings: intraplaque, inside the plaque; subintimal, between the plaque and media; and intramedial, between the media and adventitia 11) .…”
Section: Methodsmentioning
confidence: 99%
“…Intravascular imaging to support diagnosis and treatment of peripheral artery disease is becoming an important factor in new and evolving endovascular interventions. Use of such imaging can help form the treatment strategy, size the vessel so that the appropriate diameter of balloons or stents being placed is chosen, and guide and direct treatments such as angioplasty and atherectomy to minimize vessel wall injury [6,[27][28][29][30][31]. Intravascular imaging also permits assessment of tissue in the region of the procedure in order to determine whether further treatment is necessary to address regions with incomplete treatment or injury resulting from the treatment [30,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive IVUS imaging allows for greater understanding of lesion morphology, residual stenosis, adventitial injury and results in improved primary patency. [15][16][17][18] The use of IVUS in the coronary vasculature has been shown to increase luminal diameter by allowing for more accurate sizing of the vessel and thereby allowing for larger balloons to significantly improve luminal diameter without increasing dissection. 19 Aggressive debulking has been previously postulated to delay re-intervention for these femoropopliteal in-stent restenosis patients.…”
Section: Discussionmentioning
confidence: 99%